2020
DOI: 10.1103/physrevd.101.123029
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuity gravity modes in hybrid stars: Assessing the role of rapid and slow phase conversions

Abstract: Discontinuity gravity modes may arise in perturbed quark-hadron hybrid stars when a sharp density jump exists in the stellar interior, and they are a potential fingerprint to infer the existence of quark matter cores in compact objects. When a hybrid star is perturbed, conversion reactions may occur at the quarkhadron interface and may have a key role in global stellar properties such as the dynamic stability and the quasinormal mode spectrum. In this work we study the role of the conversion rate at the interf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 58 publications
11
41
0
2
Order By: Relevance
“…The error related to the fundamental mode is reduced as the compactness of the NS increase, but it is never larger than 20% [78]. On the other hand, if we focus on the error associated to the g modes, the difference is less than 10% [74,79]. Therefore, for the g modes, the results obtained using the relativistic Cowling approximation are qualitatively and quantitatively acceptable.…”
Section: Relativistic Cowling Approximationmentioning
confidence: 88%
See 1 more Smart Citation
“…The error related to the fundamental mode is reduced as the compactness of the NS increase, but it is never larger than 20% [78]. On the other hand, if we focus on the error associated to the g modes, the difference is less than 10% [74,79]. Therefore, for the g modes, the results obtained using the relativistic Cowling approximation are qualitatively and quantitatively acceptable.…”
Section: Relativistic Cowling Approximationmentioning
confidence: 88%
“…The presence of g modes in cold and non rotating stars, indicates that exist an abrupt phase transition in the interior of the star, because these modes are completely inhibited if the EoS is continuous [73]. Also, it is important to stress that the g modes associated with discontinuities in the EoS only exist in the slow conversion scenario: g modes does not appear if the conversion is rapid [74].…”
Section: Non-radial Oscillationsmentioning
confidence: 99%
“…As stressed previously, nucleation timescales can decrease significantly for hot NSs. It has been suggested that they may be smaller than typical perturbation timescales for temperatures around 20 MeV (Tonetto & Lugones 2020). In this case, conversions around a phase-splitting surface should be rapid.…”
Section: Boundary and Matching Conditions To Elastic Hybrid Starsmentioning
confidence: 98%
“…In this work, we focus our attention on the study and analysis of the g-modes associated with discontinuous energy density profiles inside the compact star. For these modes, the relativistic Cowling approximation gives quantitatively accurate value of the frequencies, with errors not larger that ∼10% when compared to those calculated using linearized perturbation theory (Tonetto & Lugones 2020).…”
Section: Non-radial Oscillationmentioning
confidence: 81%